La “cicatriz” de la libertad - Stamile, Natalina (Derecom. Revista Internacional de Derecho de la Comunicación y de las Nuevas Tecnologías, 2024)
The aim of this article is to extricate, although somewhat briefly, the thoughts of Vasilij Grossman, especially in relation to his work "Tutto scorre". I will argue that he was able to conjure up such a novel because he was essentially a free spirit. My claim is that it is not a novel of interest just for aesthetic reasons, particularly for the way the life of the main character is narrated, but for its implications for practical ethics, because it sheds light on a philosophical understanding of reality, in the tradition of “Lebensphilosophie”. To sump up my argument: “Tutto scorre” is a denounciation of the crimes committed by Russians and Germans during the XX century.